The Influence of Environmental, Social, Economic, and Media Factors on Public Opinion Toward Coal Mining and Shipping Businesses - Hani, Muhammad; Pradana, Mahir (eProceedings of Management, 2026)
This study analyzes how environmental, social, economic, and media factors affect public opiniontoward coal mining and shipping industries in Indonesia. Using quantitative methods and Partial LeastSquare-Structural Equation Modeling (PLS-SEM), data from 80 respondents were evaluated alongsidesentiment analysis of 100 digital media comments. Results indicate that environmental and media factorssignificantly influence public support or opposition, while social and economic considerations comparativelylack significant impact. The implication is that industry and policymakers seeking greater public trust mustprioritize transparent environmental stewardship and effective media communication.Keywords—public opinion, coal industry, shipping, environmental perceptions, digital sentiment analysis.